2022
DOI: 10.1101/2022.09.20.508739
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The logic of recurrent circuits in the primary visual cortex

Abstract: Recurrent cortical activity sculpts visual perception by refining, amplifying, or suppressing incoming visual signals. Despite the importance of recurrent circuits for cortical processing, the basic rules that govern how nearby cortical neurons influence each other remains enigmatic. We used two-photon holographic optogenetics to activate ensembles of neurons in Layer 2/3 of the primary visual cortex (V1) in the absence of external stimuli to isolate the impact of local recurrence from external inputs. We find… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 58 publications
5
28
0
Order By: Relevance
“…We used this measure to calculate the influence of the photostimulation of a given target neuron on the nontargeted neurons located within a 300µm radius. We found, in line with previous reports (5962), that the influence of photostimulation of a given neuron is positive for nearby neurons, and negative for neurons up to 200µm away (Figure 5C). Interestingly, this influence profile with respect to distance was maintained during the interictal state, and there was no significant difference in the influence measure between baseline and interictal (2-way ANOVA; distance to target: p< 1e-27; trial state: p> 0.05).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We used this measure to calculate the influence of the photostimulation of a given target neuron on the nontargeted neurons located within a 300µm radius. We found, in line with previous reports (5962), that the influence of photostimulation of a given neuron is positive for nearby neurons, and negative for neurons up to 200µm away (Figure 5C). Interestingly, this influence profile with respect to distance was maintained during the interictal state, and there was no significant difference in the influence measure between baseline and interictal (2-way ANOVA; distance to target: p< 1e-27; trial state: p> 0.05).…”
Section: Resultssupporting
confidence: 93%
“…These studies have found a consistent, spatially-dependent effect of optogenetic photostimulation of a given neuron on the activity of surrounding non-targeted neurons within 200µm in cortex. This functional effect of photostimulated cells on neighbouring neurons is likely borne out of the reciprocal, multisynaptic anatomical connectivity of excitatory and inhibitory neurons within cortex (59, 62, 6466). To characterise whether this structure of neural circuit excitability is affected in the epileptic state, we analysed the photostimulation-evoked responses of non-targeted neurons across baseline and acute epilepsy.…”
Section: Resultsmentioning
confidence: 99%
“…4-4 ). These results are in agreement with evidence that cell-specific stimulation drives localized activity in nearby cells within a distance of <40 µm ( Packer et al, 2015 ; Oldenburg et al, 2022 ).…”
Section: Resultssupporting
confidence: 91%
“…When giving input to larger numbers of neurons (e.g., 50), it might be expected that response reliability would be lower than when driving smaller numbers of neurons (e.g., 20, Fig. 4 A–D ) because of recurrent network effects when some stimulated neurons affect other nearby cells ( Marshel et al, 2019 ; Dalgleish et al, 2020 ; O’Rawe et al, 2022 ; Oldenburg et al, 2022 ). We also find more off-target activation in nearby cells when using 50 stimulation targets (45/298 unstimulated cells above a 7.5% ΔF/F 0 threshold, Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to excitatory recurrence, photostimulation of cortical neurons in vS1 L2/3 engages strong feedback inhibition within a few milliseconds that typically lasts up to ∼50 ms (Mateo et al, 2011). Moreover, though L2/3 pyramidal neurons with near-identical tuning amplify one another’s responses, the dominant interaction among neurons with even slightly different tuning is mutual suppression (Chettih and Harvey, 2019; Oldenburg et al, 2022). Such inhibition is likely to suppress responses, especially among downstream (i.e., opsin non-expressing) neurons.…”
Section: Discussionmentioning
confidence: 99%